2023
DOI: 10.1111/jppi.12469
|View full text |Cite
|
Sign up to set email alerts
|

Personal emergency response systems and people with intellectual and developmental disabilities in the United States

Carli Friedman

Abstract: Personal Emergency Response Systems (PERS) are electronic medical alert devices that help people with intellectual and developmental disabilities (IDD) receive assistance in emergencies. According to research on older adults, PERS improve health outcomes, provide people with a sense of security and peace of mind, promote independence, and prevent institutionalization. The aim of this study was to examine if, and how, states provided PERS to people with IDD in their Medicaid Home and Community Based Services (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…This research represents the perspective of people with intellectual disabilities about their own UK general election experiences within the academic literature for the first time, building on previous academic research which does so beyond the UK (Agran et al, 2016; Friedman, 2018; Friedman, 2019; Kjellberg & Hemmingsson, 2013) and considering the Scottish Independence referendum (Willis et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This research represents the perspective of people with intellectual disabilities about their own UK general election experiences within the academic literature for the first time, building on previous academic research which does so beyond the UK (Agran et al, 2016; Friedman, 2018; Friedman, 2019; Kjellberg & Hemmingsson, 2013) and considering the Scottish Independence referendum (Willis et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Despite this interest, there has been limited voting research directly involving people with intellectual disabilities. Globally, people with intellectual disabilities have been involved in interviews conducted by Kjellberg and Hemmingsson (2013) in Sweden and focus groups conducted by Friedman (2018, 2019) plus semi‐structured interviews conducted by Agran et al (2016) in the United States. In the United Kingdom, Willis et al (2016) reported on focus groups concerning the Scottish Independence referendum and Chadwick et al (2017) published an easy‐read report about focus groups and interviews concerning the 2015 general election.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation